Moving through migrant psychiatry: asylum seeking in Europe, forced mobility, and anthropology as interdisciplinary intervention - Khan, Nichola (Frontiers in Psychiatry, 2025)
This perspective reflects on the relationship between migrant psychiatry and asylum seeking in Europe, drawing on anthropological fieldwork in a public migrant psychiatry clinic and mobile psychiatry teams serving asylum seekers, refused asylum seekers, and homeless migrants in France. Restrictive EU migration policies have produced protracted forms of “wandering” that may last for years; a sedentarist emphasis in national migrant services has generally not kept pace. Calls by international agencies to protect the mental health of refugees and displaced people are conflicting with a hostile policy backlash by national governments, delimiting a contradictory situation. This perspective discusses ways movements of migrants across countries and discontinuous and uneven healthcare and asylum infrastructures are shaping clinical expressions of illness and intervention and the asylum clinic as a critical site of inquiry. It develops on anthropology as an interdisciplinary intervention that can more roundly align ways in which migrant patients, clinical services, and professionals move across sectoral boundaries, account for contested political fields and multiple registers of interpretation, and answer some questions arising at their juncture.